Assessing the influence of COVID-19 on influenza prevalence: A multicenter time series study - Khalid Bin Saleh; Hisham A. Badreldin; Tariq Alqahtani; Nada Alsuhebany; Shuroug A. Alowais; Khalid Al Sulaiman; Mohammed Alrashed; Yara Alsaeed; Abdulrahman Alyousef; Rema Aldugiem; Ohoud Aljuhani; Naif Alharbi; et al. (Elsevier, 2023)
Background: During the COVID-19 pandemic, countries around the world implemented various interventions to manage the spread of respiratory illnesses, including influenza. However, there is a lack of studies that have assessed the influence of COVID-19 on influenza prevalence in Saudi Arabia. In this study, we aimed to evaluate the prevalence of positive influenza cases before and during the COVID-19 pandemic in relation to the mitigation measures and policy initiatives in Saudi Arabia. Methods: A multicenter, time-series cross-sectional study was conducted to evaluate influenza prevalence before and during the COVID-19 pandemic between 01/01/2017 and 31/12/2021. This study included all patients who were screened for influenza infection at healthcare facilities across Saudi Arabia using polymerase chain reaction (PCR). The primary outcome was to determine the prevalence of influenza infections before and during the COVID-19 pandemic, while the secondary outcome was to describe the demographic data and comorbidities of the included patients in both periods. Results: During the study period, 5238 cases were identified based on a positive PCR result for influenza virus. The yearly number of influenza cases in the pre-COVID-19 period was 1123 (2.03 %), 1075 (1.63 %), and 1883 (2.20 %) cases in 2017, 2018, and 2019, respectively. On the other hand, the number of cases during the COVID-19 pandemic was 417 (0.63 %) and 740 (1.27 %) in 2020 and 2021, respectively, with a comparable number of performed tests. Patients infected with the influenza virus between 2020 and 2021 were older than patients who were infected before the COVID-19 pandemic. Conclusion: The study found a lower number of influenza cases during the COVID-19 pandemic, with no clear peak during November and December 2020 and 2021.